High consumption of unhealthy commercial foods and beverages tracks across the complementary feeding period in rural/peri‐urban Cambodia - Guy‐Marino Hinnouho; Elaine L. Ferguson; Amy MacDougall; Hou Kroeun; Prak Sophonneary; Mary Chea; Alissa M. Pries (Maternal and Child Nutrition, 2023)
Abstract Consumption of unhealthy commercial foods and beverages (UCFB) is common among infants and young children living in low‐ and middle‐income countries. Such foods can displace other nutritious foods, however, there is limited evidence on how this consumption tracks across time. This study assessed and tracked UCFB consumption of children living in rural/peri‐urban Cambodia during the complementary feeding period, identified UCFB consumption patterns of these children, and explored the association between UCFB consumption and growth. A 6‐month longitudinal cohort study was implemented among 567 caregivers of children aged 10–14 months at recruitment. UCFB consumption was estimated each month via a telephone‐administered 7‐day food frequency questionnaire, and UCFB consumption patterns were identified based on changes in this frequency of consumption over time. The majority of children either maintained (45.7%, n = 246) or developed (43.5%, n = 234) an unhealthy consumption pattern and only 10.8% (n = 58) of children maintained/transitioned into a healthy consumption pattern. High consumers of UCFB at 10–14 months had a 4.7 (CI: 4.7 [3.1–7.2]) times odds of being high consumers of UCFB at 15–19 months (p < 0.001). There was a trend of lower length‐for‐age z‐scores (LAZ) among children maintaining or developing an unhealthy consumption pattern (~−0. SD LAZ) compared to children maintaining/transitioning into a healthy consumption pattern, however, this association was not statistically significant. Findings indicate that high UCFB consumption begins during infancy and tracks into early childhood. National policies and programmes centred on early interventions addressing the use of UCFB for infant and young child feeding are needed.